The Lucky Ones : One Family and the Extraordinary Invention of Chinese America - Expanded paperback Edition - Ngai, Mae M. (Book collections on Project MUSE., 2010)
Traces three generations of a Chinese-American family from its patriarch's self-invention as an immigration broker in post-gold rush San Francisco to the family's intimate involvement in the 1904 World's Fair.